The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/dom.12920
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness and safety of different basal insulins in a real‐world setting

Abstract: In a real-world clinical setting in China, treatment with long-acting insulin analogues was associated with better glycaemic control, as well as less hypoglycaemia and weight gain than treatment with NPH insulin in type 2 diabetes patients. However, the clinical relevance of these observations must be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
8
0
3
Order By: Relevance
“…Previous ORBIT study has shown that the average HbA1c level of onset insulin therapy in T2D in China was 9.6%. [11][12][13] However, this does not meet the recommendation of the Chinese guidelines for the prevention and treatment of T2D that patients with HBA1c levels above 7% of the oral medicines that do not meet the standard should start insulin therapy, 14 which suggested that the current situation of using basic insulin in clinic is late and clinical inertia exists. Therefore, the timing of initial treatment of basic insulin is particularly important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous ORBIT study has shown that the average HbA1c level of onset insulin therapy in T2D in China was 9.6%. [11][12][13] However, this does not meet the recommendation of the Chinese guidelines for the prevention and treatment of T2D that patients with HBA1c levels above 7% of the oral medicines that do not meet the standard should start insulin therapy, 14 which suggested that the current situation of using basic insulin in clinic is late and clinical inertia exists. Therefore, the timing of initial treatment of basic insulin is particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in more than 40% of these patients, the insulin dosage did not change during the first 3 months of basal insulin treatment. [11][12][13] Therefore, we carried out this program, by using the mobile health application (APP) in basal insulin optimal management program for insulin-naive T2D patients in China, the effectiveness of this kind of education in telemedicine was to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The ORBIT prospective study, conducted in China between 2011 and 2013, provided insight into results of basal insulin treatment in a large cohort (16,341 patients completed 6 months follow-up) of Chinese patients with T2DM inadequately treated with OAMs [ 30 , 39 ]. Baseline HbA1c levels were high [mean HbA1c among patients starting basal insulin therapy was 9.6% (81 mmol/mol)] [ 30 ]. Among patients with available data after 3 and 6 months of therapy, glycemic control improved significantly at 6 months with an overall reduction in HbA1c of 2.1% (23 mmol/mol) [2.2% (24 mmol/mol) in the IGlar cohort].…”
Section: Real-world Use Of Insulin Glargine In East Asiansmentioning
confidence: 99%
“…Among uncontrolled patients, more than 30% did not report dose titration between consecutive visits [ 39 ]. The study results indicate that initiation of basal insulins in a real-world setting was associated with minor weight gain (0.10 kg over 6 months in the entire study cohort, 0.09 kg in an IGlar cohort [ 30 ]) and no significant increase in hypoglycemia risk from before basal insulin initiation to 6 months after initiation [ 39 ]. The rate of general hypoglycemia was significantly lower in patients treated with IGlar vs insulin detemir or NPH insulin [ 30 ].…”
Section: Real-world Use Of Insulin Glargine In East Asiansmentioning
confidence: 99%
See 1 more Smart Citation